Formalism Analysis on the Novel Androphobia by Ullan Pralihanta - T. Takwa; R. Rosdiana (Universitas Sembilanbelas November Kolaka, 2017)
Formalism is the main concept used as an analysis material. In formalism there are two aspects studied (1) formal aspects of language and (2) storytelling techniques. The formal aspects of language relate to five aspects, namely (1) title, (2) point of view, (3) style and tone, (4) symbolism, and (5) irony. The storytelling technique deals with three aspects, namely (1) fabula, (2) sujet and (3) motif. This study focuses on storytelling techniques. Fabula or stories relate to sequences of events in order sorted in causality relationships. In the novel Androphobia by Ullan Pralihanta is divided into 3 parts, namely (1) episodes of love Yasmin─Ovan, (2) episodes of love Robin─Gadis, and (3) episodes of shrinkage. Sujet is a plot, a narrative structure, that is the way semantic material presentation in a text in Androphobia, a novel by Ullan Pralihanta uses a forward plot with several flashes of events. The forward plot occurs 2 times, that is, (1) the events of part 1, part 2, part 3, part 5, and part 15, (2) the events of section 6, section 7, sections 9, 10 to section 19. The flashy event occurs in Section 15 to Section 6.